2020
DOI: 10.1017/dmp.2020.397
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impairment and Coping Strategies During the COVID-19 Pandemic Among Students in Pakistan: A Cross-Sectional Analysis

Abstract: High levels of stress are expected when crises affect people’s lives. Therefore, this web-based, cross-sectional study was conducted among university students from Pakistan to investigate the psychological impairment and coping strategies during COVID-19 pandemic. Google forms were used to disseminate the online questionnaire to assess anxiety (Generalized Anxiety disorder-7), depression (Patient Health Questionnaire-9) and the coping strategies (Brief-COPE). A total of 1134 responses (age 21.7±3.5 years) were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
79
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(101 citation statements)
references
References 16 publications
17
79
4
1
Order By: Relevance
“…The most frequently used coping strategies in our sample were acceptance, self-distraction, and emotional support. Similar results were found among health and social workers ( 53 ) and students ( 54 ). Accepting that the stressor is happening and learning to live with it could be viewed as an adaptive mechanism in a global pandemic.…”
Section: Discussionsupporting
confidence: 85%
“…The most frequently used coping strategies in our sample were acceptance, self-distraction, and emotional support. Similar results were found among health and social workers ( 53 ) and students ( 54 ). Accepting that the stressor is happening and learning to live with it could be viewed as an adaptive mechanism in a global pandemic.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings show that LP and PH, LP and PsH, LP and OW, and LP and PA also found statistically significant negative relationships as their p-values were <0.05. Similarly, a study conducted in Pakistan reported that the COVID-19 negatively influenced Pakistani students, further linked with high depression and mental anxiety (Salman et al, 2020). Likewise, a study conducted in Canada reported that outdoor and overall PA decreased due to the lockdown (Lesser and Nienhuis, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…This difference in data could be due to the distinct speed at which the virus spread between provinces. In Pakistan, one work indicated that 34% of students reported moderate to severe anxiety symptoms [ 48 ]. Their data are similar to those obtained in a study conducted in Turkey to explore anxiety-related symptoms (45%) [ 49 ].…”
Section: Discussionmentioning
confidence: 99%